Communication strategies among promoters during MATTA Fair 2025 - Mohamad Isa, Abdul Azim; Hashimee, Muhammad; Abdul Rashid, Khadijah Khalilah; Nordin, Fitri Nurul 'Ain; Hazeman, Muhammad Nursafwan; Zakiyah, Fitri (RSIS International, 2025)
Communication is a crucial strategy in promoting products and packages. The aim of this research is to discover the different types of communication strategies used by promoters during MATTA Fair 2025. Different communication strategies are performed by tour package promoters when engaging with local customers who love travelling from diverse backgrounds and preferences. Specific circumstances also evoke the kinds of communication employed when encountering scenarios that trigger some suitable strategies. This study uses a qualitative research method based on observations conducted at MITEC, Kuala Lumpur during MATTA Fair 2025. The findings from this study are expected to help tour package promoters increase sales through appropriate types of communication according to the background of tourists.